Manejo de Rottboellia exaltata (Loureiro) W. D.Clayton através da interação e eficácia de herbicidas em cana-de-açúcar - Ramos, Gustavo da Cunha (Universidade Federal de São Carlos, 2023)
One of the major limitations in the proper management of weeds is the lack of knowledge about how to control weeds correctly before and after the installation of our crop of interest. In this context, the species Rottboellia exaltata (camelote grass) is showing a significant increase in its infestations in sugarcane cultivated areas. Therefore, the objective was to evaluate the effectiveness and interaction of herbicides applied post-emergence diquat (400 g.i.a.ha-1) and glyphosate (1175 g.i.a.ha-1) in association with herbicides applied pre-emergence pendimenthalin (1200 g.i.a.ha -1), clomazone (1000 g.i.a.ha-1), indaziflam (100 g.i.a.ha-1) and trifluralin (900 g.i.a.ha-1), in the control of Rottboellia exaltata after tillering of the species, with 3 fully expanded leaves, in addition to to analyze by means of a reseeding before the application of herbicides the control of the interaction of the treatments in the germination of the species. The experiments were carried out in a greenhouse in a completely randomized design in a 15 x 6 factorial scheme with four replications, with 14 treatments including post and pre-emergence herbicides and a control without herbicide application, and the second factor consisted of six evaluations (7, 14, 21, 28, 35, 42 DAA). It was possible to conclude through this work that the interaction and association between desiccant and residual herbicides proved to be the best way to control Rottboellia exaltata, being in short importance for its management. The treatments of diquat+pendimenthalin, diquat+clomazone, diquat+indaziflam, diquat+trifluralin, glyphosate+pendimenthalin, glyphosate+clomazone, glyphosate+indaziflam and glyphosate+trifluralin controlled 100% of the species and showed 0% germination of Rottboellia exaltata plants.
Management of Rottboellia exaltata (Loureiro) W. D.Clayton through the interaction and effectiveness of herbicides in sugarcane
Keywords: Associação herbicidas; Controle; Germinacao; Gramineas; Herbicide association; Control; Grasses; Germination; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA